Pengaruh Kualitas Produk, Kualitas Layanan dan Social Media Marketing Terhadap Keputusan Pembelian: (Studi pada Konsumen Kopi Kenangan di Rc Veteran Jakarta Selatan) - Riski Emylandi; Kartini Istikomah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to determine the impact of product quality, service quality, and social media marketing (Instagram) on purchasing decisions for consumers of Kopi Kenangan RC Veteran (drive-thru). This research is quantitative in nature. The sample consists of 100 respondents, selected using a non-probability sampling method with accidental sampling and the Lemeshow formula. Data collection was conducted through a questionnaire using a Likert scale, and the data were processed using Microsoft Excel 2019 and SPSS Software version 22. The data analysis included validity and reliability tests, classical assumption tests, hypothesis testing, and multiple linear regression. The results of this study indicate that the variables of product quality, service quality, and social media marketing each have a positive effect on purchasing decisions. Additionally, product quality, service quality, and social media marketing collectively have a positive impact on purchasing decisions